Sarcopenia, falls and mistreatment in the context of fragile Elderly Syndrome: A bibliographic literature review - Biancardi, Isabella Muniz; Carneiro, Izabella Rodrigues; Carneiro, Joaquim Junior Barros; Silva, Jullya Passarelli Ferreira da; Brandao, Sheylla Rodrigues Soares; Vinhal, Vitor Eduardo Morais; Silva, Samhuel Freitas da; Barros, Marqueyd Araujo; Prado, José Walter Lima (Seven Editora, 2023)
The frail elderly syndrome originates from the decline of the physiological functions of the elderly. Among these patients, there is a decrease in physical activities, weight loss, reduced mobility speed, and reduced cognitive functions. Currently, there is a higher prevalence of pre-frail elderly. However, with the aging of the population, an increase in frail elderly is expected. Therefore, sarcopenia, the risk of falls, and the abuse suffered with physical and psychological violence must be studied, to understand how they help in the degeneration of the functionality of the elderly. In this sense, the objective of this work is to analyze studies that have as their research object the influence of reduced muscle mass, falls, and abuse on the quality of life of frail elderly people. For this, a high-sensitivity search was performed in databases (Lilacs via the Virtual Health Library (VHL), Medline via Pubmed and Cochrane Library) using descriptors linked to the frailty syndrome of the elderly. As a result, 3,398 studies were found, of which 20 studies from eight countries were included with a total sample of 6,782 participants. It was identified that sarcopenia increases with age, stabilizing at age 80 and being more common in women, institutionalized elderly and hospitalized elderly. Regarding falls, they are the most common clinical variable in frail elderly people, being a common history in most of them. Abuse has been the subject of few studies, but it is concluded that elderly men and depression are the biggest victims of physical and verbal violence. DOI:https://doi.org/ 10.56238/devopinterscie-138